Antitumor Activity of a Polypyridyl Chelating Ligand: In Vitro and In Vivo Inhibition of Glioma. (23rd February 2015) - David, Clément N.; Frias, Elma S.; Elix, Catherine C.; McGovern, Kathryn E.; Walker, Ameae M.; Eichler, Jack F.; Wilson, Emma H.
Glioblastoma multiforme is an extremely aggressive and invasive form of central nervous system tumor commonly treated with the chemotherapeutic drug Temozolomide. Unfortunately, even with treatment, the median survival time is less than 12 months. 2, 9-Di- sec -butyl-1, 10-phenanthroline (SBP), a phenanthroline-based ligand originally developed to deliver gold-based anticancer drugs, has recently been shown to have significant antitumor activity in its own right. SBP is hypothesized to initiate tumor cell death via interaction with non-DNA targets, and considering most glioblastoma drugs kill tumors through DNA damage processes, SBP was tested as a potential novel drug candidate against glial-based tumors. In vitro studies demonstrated that SBP significantly inhibited the growth of rodent GL-26 and C6 glioma cells, as well as human U-87, and SW1088 glioblastomas/astrocytomas. Furthermore, using a syngeneic glioma model in mice, in vivo administration of SBP significantly reduced tumor volume and increased survival time. There was no significant toxicity toward nontumorigenic primary murine and human astrocytes in vitro, and limited toxicity was observed in ex vivo tissues obtained from noncancerous mice. Terminal deoxynucleotidyl transferase dUTP nick end labeling staining and recovery assays suggest that SBP induces apoptosis in gliomas. This exploratory study suggests SBP is effective in slowing the growth of tumorigenic cells in the brain while exhibiting limited toxicity to normal cells and tissues and should therefore be further investigated for its potential in glioblastoma treatment.